1989
DOI: 10.1159/000217630
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage and Lymphocyte Antibody-Dependent Cellular Cytotoxicity in Spontaneous Leukemogenesis of AKR/J Mice

Abstract: Antibody-dependent cell-mediated cytotoxicity (ADCC) mediated by peritoneal macrophages and splenic lymphocytes was studied in young (15 weeks) and old (45 ± 5 weeks) preleukemic AKR/J mice and leukemic (55 ± 5 weeks) AKR/J mice. This strain spontaneously develops a virally induced T cell leukemia-lymphoma between the ages of 32 and 48 weeks. The peritoneal macrophages from the AKR/J leukemic and old preleukemic mice showed an impaired ADCC when compared with their respective age and tumor-free BALB/c controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…mice [21,22]. Our data support the concept that in nude mice ADCC mediated by polyclonal or monoclonal antibodies directed against extracellular melanoma antigens can direct immune cells from nude mice (including NK cells, macrophages, and possibly others) to play an important role in tumor rejection [20,23]. The ADCC assay could be considered an in vitro model for in vivo experiments in which melanoma cell challenge took place following pretreatment with specific antibody, and effector cells (NK and macrophages) were attached to melanoma cells from the blood and lymphatics.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…mice [21,22]. Our data support the concept that in nude mice ADCC mediated by polyclonal or monoclonal antibodies directed against extracellular melanoma antigens can direct immune cells from nude mice (including NK cells, macrophages, and possibly others) to play an important role in tumor rejection [20,23]. The ADCC assay could be considered an in vitro model for in vivo experiments in which melanoma cell challenge took place following pretreatment with specific antibody, and effector cells (NK and macrophages) were attached to melanoma cells from the blood and lymphatics.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that NK cells and macrophages functioned as effector cells when combined with treatment of mice with a mAb, BR96, which recognizes a cell membrane antigen of a cultured human breast cancer and had cytotoxic activity in vitro and in vivo in a nude mice model [20,23]. The ADCC assay could be considered an in vitro model for in vivo experiments in which melanoma cell challenge took place following pretreatment with specific antibody, and effector cells (NK and macrophages) were attached to melanoma cells from the blood and lymphatics.…”
Section: Discussionmentioning
confidence: 99%
“…The ADCC assay used was that described by De la Fuente et al (1989). Briefly, target cells were labeled with slCr as detailed above, then washed 3 times with culture medium containing 5% FBS.…”
Section: Cytotoxicity Assaysmentioning
confidence: 80%